Investigating temperature effects on perovskite solar cell performance via SCAPS-1D and impedance spectroscopy - A. Mortadi; Y. Tabbai; E. El Hafidi; H. Nasrellah; E. Chahid; M. Monkade; R. El Moznine (Cleaner Engineering and Technology)
Perovskite solar cells (PSCs) power energy conversion is essential for addressing global energy requirements while mitigating environmental impacts. PSCs are a highly efficient and cost-effective form of photovoltaic technology but face challenges related to stability and temperature sensitivity. As temperature affects charge carrier mobility, material characteristics, and the performance of charge-selective layers, its critical to understand and manage these effects to optimize PSCs operation. The simulation software SCAPS-1D emerges as a vital tool for analyzing PSCs performance under various thermal conditions, aiding in the prediction and optimization of PSCs function for enhanced efficiency and stability.Thermal effects on PSCs are evaluated by analyzing electrical parameters, such as the current-voltage density (J-V) and power-voltage (P-V) curves, across different temperatures. These analyses are crucial to grasp the relationship between temperature, power output, and efficiency, providing insights necessary for thermally managing PSCs in real-world applications. Advancing these studies with Impedance Spectroscopy (IS) has granted a detailed view of the cells properties across frequencies, offering a deeper understanding of underlying processes like ionic transport, recombination, and diffusion. Notably, this technique uncovers the microscale impacts of temperature on these processes, informing the development of PSCs with superior thermal resilience and operational efficacy.